Introduction to an Urban Ecosystem Approach. - Grunewald, Karsten; Li, Junxiang; Xie, Gaodi; Kümper-Schlake, Lennart (Springer, 2018)
In the context of ongoing urbanization processes and sustainable urban development, the aim is to capture, describe, and convey to various target groups the current significance, the values, and the potentials of urban biodiversity and ecosystem services. To seek sustainable pathways, the current developments and different approaches are to be studied globally, whereas this book focuses on current processes and practices in China and Germany in more detail. The strategic goal is a long-term appreciation of the potentials and increased consideration of urban green spaces as nature-based solutions in city planning and development.
Keywords: Stadtentwicklung; Ökosystemleistung; Ökologie; Nachhaltige Entwicklung; Transformation; Landschaftsverbrauch; Flächennutzung; Stadtgrün; Landnutzung; Stadtökologie; Stadtnatur; Biodiversität